2010
DOI: 10.1002/anie.200906819
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Retrofunctionalization of Single‐Walled Carbon Nanotubes

Abstract: As if nothing had happened: A detailed mechanistic investigation of the nucleophilic addition of organolithium reagents onto single‐walled carbon nanotubes (SWCNTs) revealed that the initial functionalization step is part of an equilibrium. Consequently, the functionalization of the sidewalls of SWCNTs is reversible, and the introduced substituents can be detached easily by reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
3
29
0
2
Order By: Relevance
“…This is in accord with the diamagnetic shielding effect of the complexed ruthenium metal and is an expected finding for [(h 5 -Cp*)Ru(h 6 -Arene)] þ complexes [4,21,31]. The amide protons of complexes (6b and 7b) however, experience a downfield shift of 2.46 and 2.74 ppm respectively compared to the uncomplexed ligands [34,35] while the sulfonamide proton of complex (9b) is unobservable in the 1 H NMR spectrum potentially indicating its dissociation in situ. These observations are attributed to the electron withdrawing effect of the complexed [(h 5 -Cp*)Ru] þ fragment.…”
Section: Synthesis and Characterizationsupporting
confidence: 85%
“…This is in accord with the diamagnetic shielding effect of the complexed ruthenium metal and is an expected finding for [(h 5 -Cp*)Ru(h 6 -Arene)] þ complexes [4,21,31]. The amide protons of complexes (6b and 7b) however, experience a downfield shift of 2.46 and 2.74 ppm respectively compared to the uncomplexed ligands [34,35] while the sulfonamide proton of complex (9b) is unobservable in the 1 H NMR spectrum potentially indicating its dissociation in situ. These observations are attributed to the electron withdrawing effect of the complexed [(h 5 -Cp*)Ru] þ fragment.…”
Section: Synthesis and Characterizationsupporting
confidence: 85%
“…We have recently shown that alkylated, arylated, and hydrogenated graphenes with high degrees of addition on both sides of the basal plane can be prepared in this way. [16][17][18] In the case of related reductive functionalizations of carbon nanotubes and fullerenes,we [19] and others [20] have demonstrated that such reactions can be reversible.I t has not yet been shown, but it is reasonable to assume that related reversible processes such as that depicted in Scheme 1b can also play arole in graphene chemistry.Itisimportant to keep in mind that:a )covalent addition reactions on fullerenes and carbon nanotubes are monotopic (only exohedral addend binding can take place), whereas addend binding on graphene can be both monotopic (when the sheets are supported on asurface) or ditopic (in dispersion);b)exhaustive homotopic additions will eventually lead to an increase in strain energy (eclipsing addend interactions,d eviation from normal bond angles);c )ditopic addition can lead to more stable and less strained geometries,including complete strainfree graphane with an all-chair configuration of the sixmembered carbon rings. [18,21,22] It is to be expected that the degree of retrofunctionalization (Scheme 1b)r epresents an interplay between the strain energy of the graphene adduct itself and the stability of the leaving group R À .W en ow present for the first time a) ar eaction sequence that allows the successful bisfunctionalization of graphene and b) an investigation of the topicity and leaving group dependence of the retrofunctionalization.…”
mentioning
confidence: 89%
“…This is directly related to the intercalation mechanism. There exist four main routes to carry out intercalation in graphite: (i) two-zone vapor transport developed in 1981 by Dresselhaus et al [2], (ii) electrochemical intercalation, highly interesting since 1970 due to the first lithium/graphite fluoride battery system [27,28], (iii) more recently: wet chemical functionalization of graphite which was first introduced to intercalate carbon nanotubes [29][30][31] and further on adapted for graphite [32,33] looking for bulk productions of graphene, (iv) in-situ intercalation by vapor transport and subsequent annealing in UHV and HV environments [7]. The latter is an adapted version of the two-zone vapor transport method.…”
Section: Preparation Of Gicsmentioning
confidence: 99%